Development of mobile health–based self‐management support for patients with lung cancer: A stepwise approach. Issue 3 (7th February 2022) - Ni, Xiaosha; Lou, Yan; Hu, Wenyi; Wang, Hemei; Xu, Hong; Li, Shuaini; Zhou, Yunxian; Ni, Yisha
Abstract: Aim: To develop self‐management support platform on mobile for Chinese patients with lung cancer. Design: A stepwise approach with combination of methods. Methods: Literature review was carried out to construct preliminary framework and develop detailed content for self‐management modules. A semistructured interview was conducted to elicit preference in the content and platform of self‐management modules with 15 patients with lung cancer. Delphi study was performed to evaluate and improve the content of modules with 13 experts. A pilot study was conducted to test the mobile health–based self‐management support modules with 13 patients with lung cancer. Results: A social network software‐based WeChat public account "Symptom Self‐Management" for patients with lung cancer was developed and preliminarily tested with positive feedback. Three modules were designed and presented, including symptom management (cancer‐related fatigue, cough, dyspnoea, pain, nausea and vomiting), emotion management and role management. Conclusion: This study showed that patients with lung cancer have diversified supportive care needs after discharge. A bottom‐up and stepwise approach to develop mobile health–based self‐management support tool has shown to be feasible and valuable. Theory guidance, user requirement exploration, evidence‐based information and expert evaluation are key elements of the process. Implications for Practice: The WeChat Public Account "Symptom Self‐Management" could be used as sustainable platform to support patients with lung cancer in dealing with common challenges. It provides professional information, self‐assessment tools, self‐management skills and peer‐support platform. Information presented in both text and audio forms enables patients' easy access to the platform.